2009
DOI: 10.1258/phleb.2008.008057
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of interface pressure and stiffness between elastic stockings and bandages

Abstract: Short-stretch bandages can be expected to have more pronounced benefits for augmenting muscle pump than long-stretch bandages and short-stretch stockings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…Our findings showed that the SSI increased with the number of bandages. The SSI derived from our eMLB by using three bandages was 13.4 ± 7.2 mmHg, which is comparable to that achieved by short-stretch bandages (Complilan ® ), as reported by Hirai et al 9) Milic et al also suggested that a higher venous ulcer healing rate was achieved with an SSI greater than 10 mmHg. 8) This again supports the effectiveness of our eMLB using three or more bandages to treat CVI.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings showed that the SSI increased with the number of bandages. The SSI derived from our eMLB by using three bandages was 13.4 ± 7.2 mmHg, which is comparable to that achieved by short-stretch bandages (Complilan ® ), as reported by Hirai et al 9) Milic et al also suggested that a higher venous ulcer healing rate was achieved with an SSI greater than 10 mmHg. 8) This again supports the effectiveness of our eMLB using three or more bandages to treat CVI.…”
Section: Discussionsupporting
confidence: 87%
“…Hirai et al 11 measured the interface pressure of elastic stockings and bandages during posture changes and exercise. Short-stretch bandages showed a greater pressure difference between muscle contraction and relaxation, and thus a higher working pressure, compared with long-stretch bandages and short-stretch stockings.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the aim of this previous study was to compare the pressure applied by different application techniques, it was carried out for a single bandage type. Other studies were focused on the influence of bandage mechanical properties and position (supine, standing, sitting) on the interface pressure, 3,8,11,26 but as far as we know, none of them measured the stretch of the applied bandage, though it is one of the main parameters which controls the interface pressure.…”
Section: Introductionmentioning
confidence: 99%